A signal-amplifiable biochip quantifies extracellular vesicle-associated RNAs for early cancer detection. Issue 1 (December 2017) - Hu, Jiaming; Sheng, Yan; Kwak, Kwang; Shi, Junfeng; Yu, Bohao; Lee, L. James
Abstract Detection of extracellular vesicle (EV)-associated RNAs with low expression levels in early-stage cancer remains a challenge and is highly valuable. Here, we report a nanoparticle-based biochip that could capture circulating EVs without isolation, brighten encapsulated RNAs, and amplify fluorescence signals in situ in a single step. We confine catalyzed hairpin DNA circuit (CHDC) in cationic lipid-polymer hybrid nanoparticles (LPHNs) that are tethered on a chip. LPHN features a core-shell-corona structure that facilitates the transfer and mixing of CHDC with EV-associated RNAs when forming the LPHN–EV nanocomplex. CHDC is triggered upon target RNA binding and quickly generate amplified signals. The signal amplification efficiency of LPHN–CHDC is demonstrated in artificial EVs, cancer cells, and cancer cell-derived EVs. We show that LPHN–CHDC biochip with signal amplification capability could selectively and sensitively identify low expression glypican-1 mRNA in serum EVs, distinguishing patients with early- and late-stage pancreatic cancer from healthy donors and patients with benign pancreatic disease. Extracellular vesicles (EV)-associated RNAs are serum biomarkers potentially exploitable for early cancer diagnosis. Here the authors develop a catalyzed hairpin DNA circuit within a cationic lipid-polymer hybrid nanoparticle that can detect low–level EV-associated RNAs in early stage cancer patients.